2021
DOI: 10.1088/1757-899x/1031/1/012094
|View full text |Cite
|
Sign up to set email alerts
|

The leaves and stems of Cape gooseberry (Physalis peruviana L.) as an alternative source of bioactive substances

Abstract: The objective of this work was the investigation of the chemical composition of the leaves and stems of two Cape gooseberry (Physalis peruviana L.) genotypes from Bulgaria (CG-SB and CG-NB), with the view of establishing the presence of certain bioactive substances and the prospects for their use as livestock feed or cosmetic ingredients. The leaves and stems of CG-SB genotype contained 18.63% and 40.26% cellulose, respectively, and 24.83% and 13.73% protein; the respective contents in the leaves and stems of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…At 1732 cm −1 , the stretching vibration of C=O of the carboxyl group occurs, the aromatic ring's C-H stretching vibration at 2925 cm −1 , C=C vibration at 1627 cm −1 , aromatic C=C bond at 1430 cm −1 , unsymmetric stretching of the C-O-C bridge bond and C-O-C cyclic ether at 1154 and 1102 cm −1 , respectively 27 . These bands are similar to those of ferulic acid, isolated from CgL leaf extract 28,29 . Figure 2 shows the major chemical constituents of Fen and CgL extracts.…”
Section: Resultssupporting
confidence: 72%
“…At 1732 cm −1 , the stretching vibration of C=O of the carboxyl group occurs, the aromatic ring's C-H stretching vibration at 2925 cm −1 , C=C vibration at 1627 cm −1 , aromatic C=C bond at 1430 cm −1 , unsymmetric stretching of the C-O-C bridge bond and C-O-C cyclic ether at 1154 and 1102 cm −1 , respectively 27 . These bands are similar to those of ferulic acid, isolated from CgL leaf extract 28,29 . Figure 2 shows the major chemical constituents of Fen and CgL extracts.…”
Section: Resultssupporting
confidence: 72%
“…Numerous research reported that bioactive terpenoids are associated with anti-diabetic properties. Betulinic acid, camphene, myrcene, fenchone, limonene, α-phellandrene, carvone, spathulenol, caryophyllene oxide, germacrene D, α-pinene, β-caryophyllene, α-humulene, catechin, phytol, carvacrol, hexahydrofarnesyl acetone, (E)-β-ionone are found in various Ecuadorian medicinal plants, for instance, Cajanus cajan [88], Costus comosus [102], Croton wagneri [55], Foeniculum vulgare [103], Glycyrrhiza glabra [104], Ipomoea carnea [30], Myroxylon peruiferum [105], Persea americana [31,94], Physalis peruviana [106], Matricaria chamomilla [107], Piper crassinervium [108], Siparuna eggersii [74], Urtica dioica [109] which are used traditionally for their anti-diabetic properties.…”
Section: Active Compounds Of Ecuadorian Medicinal Plants and Their An...mentioning
confidence: 99%
“…Numerous research studies have reported that bioactive terpenoids are associated with anti-diabetic properties. Betulinic acid, camphene, myrcene, fenchone, limonene, α-phellandrene, carvone, spathulenol, caryophyllene oxide, germacrene D, α-pinene, β-caryophyllene, α-humulene, catechin, phytol, carvacrol, hexahydrofarnesyl acetone, and (E)-β-ionone are found in various Ecuadorian medicinal plants; for instance, Cajanus cajan [ 89 ], Costus comosus [ 114 ], Croton wagneri [ 55 ], Foeniculum vulgare [ 115 ], Glycyrrhiza glabra [ 116 ], Ipomoea carnea [ 30 ], Myroxylon peruiferum [ 117 ], Persea americana [ 31 , 109 ], Physalis peruviana [ 118 ], Matricaria chamomilla [ 119 ], Piper crassinervium [ 120 ], Siparuna eggersii [ 74 ], and Urtica dioica [ 120 ], which are traditionally used for their antidiabetic properties.…”
Section: Bioactive Compounds Of Ecuadorian Medicinal Plants and Their...mentioning
confidence: 99%
“…This bioactive compound is also found in Foeniculum vulgare [ 103 ]. n-Hexacosane is a natural alkane that improves blood glucose levels, glucose tolerance, glycated hemoglobin, and liver glycogen [ 129 ] found in Physalis peruviana [ 118 ]. The polysaccharide holocellulose and organic polymer lignin are found in Juglans neotropica [ 130 ].…”
Section: Bioactive Compounds Of Ecuadorian Medicinal Plants and Their...mentioning
confidence: 99%